Evaluation of changes in the range of μ angle in 6-17 year-old students with normal occlusal relationship - Saied Sadeghian; Maryam Hajiahmadi; Ladan Khorrami; Alireza Eshghi (Isfahan University of Medical Sciences, 2012)
Abstract Introduction: Measuring the antero-posterior jaw relationship has an important role in thediagnosis and treatment planning in orthodontics. Common linear and angular measurements to evaluate sagittal jaw relationship, including ANB angle and Wits index are not very accurate because various factors influence them. The aim of this study was to evaluate µ angle range in 6-17 year-old students with normal occlusal relationships in Isfahan.Materials and Methods: In this descriptive-analytical study, the files in the archives of theOrthodontics Department, Isfahan Faculty of Dentistry, were evaluated and 218 cephalometric radiographs from the files of patients with no orthodontic treatment were selected; the subjects were considered to have normal occlusal relationships based on 13 criteria. The subjects were divided into 5 age groups. After tracing the cephalometric radiographs, ANB angle, Wits index and µ angle (the angle produced by the AB line intersecting the line perpendicular from A to mandibular plane) were measured and the means, standard deviations and changes in the ranges of these angles were determined. Data was analyzed by t-test, ANOVA and Pearson's and Spearman's correlation coefficients using SPSS software (α=0.05).Results: The results showed a mean of 17.34 ± 3.74º for β angle with a range of 8-27º. T-test showed significant differences in μ angle between males and females (p value = 0.021). In addition there was no significant relationship between this angle and age (p value > 0.05). There was an inverse and significant relationship between AB angle and Wits index.Conclusion: It was concluded that µ angle is accurate in evaluating antero-posterior jaw relationship and can be used as a valuable index in evaluations. Key words: Cephalometery, Dental occlusion, Orthodontics